Molecular Diagnosis of Congenital Adrenal Hyperplasia in Iran: Focusing on CYP21A2 Gene - Rabbani, Bahareh (Tehran University of Medical Sciences, 2011)
Congenital adrenal hyperplasia (CAH) is characterized by impaired biosynthesis of cortisol. 21-hydroxylase deficiency is the most common cause of CAH affecting 1 in 10000-15000 live births over the world. The frequency of the disorder is very high in Iran due to frequent consanguineous marriages. Although biochemical tests are used to confirm the clinical diagnosis, molecular methods could help to define accurate diagnosis of the genetic defect. Recent molecular approaches such as polymerase chain reaction based methods could be used to detect carriers and identify different genotypes of the affected individuals in Iran which may cause variable degrees of clinical expression of the condition. Molecular tests are also applied for prenatal diagnosis, and genetic counseling of the affected families. Here, we are willing to delineate mechanisms underlying the disease, genetic causes of CAH, genetic approaches being used in the country and recommendations for health care improvement on the basis of the molecular and clinical genetics to control and diminish such a high prevalent disorder in Iran. Also, the previous studies on CAH in Iran are gathered and a diagnostic algorithm for the genetic causes is proposed.